Cardio-renal outcomes and the direct medical cost of type 2 diabetes patients treated with sodium glucose cotransporter-2 inhibitors and glucagon-like peptide-1 receptor agonists: A population-based cohort study. (October 2021) - Tang, Eric Ho Man; Wong, Carlos King Ho; Lau, Kristy Tsz Kwan; Fei, Yue; Cheung, Bernard Man Yung
Highlights: This is a population-based study to compare the cost-effectiveness of initiating sodium glucose cotransporter-2 inhibitors (SGLT2i) versus glucagon-like peptide-1 receptor agonists (GLP-1RA) for patients with type 2 diabetes. SGLT2i users were observed to have a significantly lower risk of heart failure. SGLT2i users were observed to have better control in clinical parameters. The 1-year direct medical costs spent by SGLT2i and GLP-1RA users were comparable. Abstract: Aims: To compare cardio-renal outcomes and incurred direct medical costs of patients initiating sodium glucose cotransporter-2 inhibitors (SGLT2i) versus glucagon-like peptide-1 receptor agonists (GLP-1RA). Methods: A population-based cohort of patients with type 2 diabetes was identified from Hong Kong Hospital Authority. Patients who were free from cardiovascular and end-stage renal diseases at baseline, and newly treated with SGLT2i (n = 2, 541) or GLP-1RA (n = 303), were included. Risks of developing cardio-renal complications, incurred direct medical costs, and changes in clinical parameters were assessed between groups. Results: Over a median follow-up of 12.5 months in SGLT2i group and 25.5 months in GLP-1RA group, SGLT2i users were associated with significantly lower risk of heart failure compared with those on GLP-1RA [hazard ratio = 0.183, 95 %CI = (0.045, 0.745)]. 1-year change in clinical parameters also favored use of SGLT2i over GLP-1RA, where the former was associated with a larger reduction in fasting glucose level [difference-in-difference = −0.87 mmol/L, 95 %CI = (−1.42, −0.33), p = 0.002]. The two groups had comparable direct medical costs after 1-year of follow-up. Conclusion: Patients initiating SGLT2i experienced a significantly lower risk of heart failure than those on GLP-1RA, alongside better glycemic control through a larger reduction in fasting glucose level over one-year follow-up, while direct medical cost incurred was comparable to that of GLP-1RA.